1990
DOI: 10.1210/jcem-70-5-1426
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of Low Dose Etomidate: Correction of Hypercortisolemia in Patients with Cushing's Syndrome and Dose-Response Relationship in Normal Subjects

Abstract: To investigate the adrenostatic potential of a nonhypnotic low dose etomidate infusion, we administered 0.03 mg/kg etomidate in a bolus injection, followed by constant infusion of 0.3 mg/kg.h for 24 h to 6 patients with severe Cushing's syndrome. The dose-response relationship also was determined in 15 normal subjects. Three groups of 5 received, respectively, doses of 0.03, 0.1, and 0.3 mg/kg.h etomidate for 5 h after an initial bolus dose of 0.03 mg/kg. The response to exogenously administered ACTH [0.25 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 16 publications
1
85
1
1
Order By: Relevance
“…Rarely, parental etomidate (anesthetic induction agent) was used in refractory cases to rapidly reduce supraphysiological cortisol levels but requires careful dose-titration. 91 …”
Section: Steroidogenesis Inhibitorsmentioning
confidence: 99%
“…Rarely, parental etomidate (anesthetic induction agent) was used in refractory cases to rapidly reduce supraphysiological cortisol levels but requires careful dose-titration. 91 …”
Section: Steroidogenesis Inhibitorsmentioning
confidence: 99%
“…2). It is the only parenteral steroidogenesis inhibitor available and provides rapid hypercortisolemia control , Schulte et al 1990). An i.v.…”
Section: Etomidatementioning
confidence: 99%
“…An i.v. bolus injection of etomidate at a low non-hypnotic dose (0.03 mg/kg) followed by constant infusion of 0.3 mg/kg per h for 24 h (Table 3) decreases serum cortisol in a dose-dependent manner with significant suppression after the first 5 h with a maximum effect after 11 h , Schulte et al 1990. Glucocorticoid replacement to prevent adrenal insufficiency is warranted after 24 h of etomidate infusion.…”
Section: Etomidatementioning
confidence: 99%
“…Interestingly, in two patients sustained remission was observed after cessation of ketoconazole and metyrapone, which may in part be explained by effects of these drugs on tumoral ACTH secretion (Sharma & Nieman 2012). Finally, in the intensive care setting, the anesthetic drug etomidate, at dosages between 0.1 and 0.3 mg/kg per h, can be used to rapidly suppress cortisol production in complicated EAS (Schulte et al 1990).…”
Section: Ectopic Acth Syndromementioning
confidence: 96%
“…Originally used as an anesthetic agent, etomidate, which is administered i.v., was soon reported to cause adrenocortical insufficiency in critically ill patients (Fellows et al 1983). Subsequent studies showed that etomidate can be used to induce eucortisolemia in patients with CS (Schulte et al 1990, Krakoff et al 2001. Its suggested mechanism of action is inhibition of the 11b-hydroxylase and cholesterol side-chain cleavage enzymes (Lamberts et al 1987, Schteingart 2009).…”
Section: Inhibitors Of Adrenocortical Steroidogenesismentioning
confidence: 99%